Improving Madrasah Competitiveness Through Excellent Islamic Education Development Strategies - Zakariyah, Zakariyah (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2024)
This study analyzes the development strategy of superior Islamic education at Madrasah Aliyah Unggulan Amanatul Ummah (MAU Amanatul Ummah) Mojokerto. This article uses case study research to reveal the comprehensive and integrative efforts made by MAU Amanatul Ummah to realize the vision of superior, intact, and noble Islamic education. The results showed that the development strategy implemented by MAU Amanatul Ummah includes institutional strengthening, improving the quality of human resources, developing a holistic curriculum, varying learning programs, implementing a comprehensive evaluation system, and strengthening networks and partnerships. The success of MAU Amanatul Ummah is inseparable from the visionary and transformative leadership of the Kiai, as well as the commitment of the entire academic community to continue to innovate and pursue excellence. Although still facing some challenges, the experience of MAU Amanatul Ummah can be an inspiration and reference for the development of Islamic education in Indonesia, especially in the context of pesantren-based education. This research contributes to the development of Islamic education discourse and practice in Indonesia and opens space for further study.